2021
DOI: 10.3390/jcm10112492
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Surgical Aortic Valve Replacement in Patients with Rheumatoid Arthritis

Abstract: Patients with rheumatoid arthritis (RA) have increased risk of developing cardiovascular disease and events. Little is, however, known about the influence of RA to the outcomes after surgical aortic valve replacement (SAVR). Methods: In a retrospective, nationwide, multicenter cohort study, RA patients (n = 109) were compared to patients without RA (n = 1090) treated with isolated SAVR for aortic valve stenosis. Propensity score-matching adjustment for baseline features was used to study the outcome difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…After linking with CMS data to capture valvular interventions performed outside the VHA, RA was associated with an increased risk of any aortic valve intervention (AHR, 1.34; 95% CI, 1.22-1.48), including both SAVR (AHR, 1.30; 95% CI, 1.16-1.45) and TAVR (AHR, 1.53; 95% CI, 1.26-1.85), suggesting a more severe AS disease course that required more frequent procedural intervention. This is of particular concern since patients with RA who underwent SAVR experienced poorer postoperative outcomes in 1 study . Aggregate inpatient costs per patient undergoing SAVR or TAVR exceeded $60 000 at 6 to 12 months postoperatively …”
Section: Discussionmentioning
confidence: 98%
“…After linking with CMS data to capture valvular interventions performed outside the VHA, RA was associated with an increased risk of any aortic valve intervention (AHR, 1.34; 95% CI, 1.22-1.48), including both SAVR (AHR, 1.30; 95% CI, 1.16-1.45) and TAVR (AHR, 1.53; 95% CI, 1.26-1.85), suggesting a more severe AS disease course that required more frequent procedural intervention. This is of particular concern since patients with RA who underwent SAVR experienced poorer postoperative outcomes in 1 study . Aggregate inpatient costs per patient undergoing SAVR or TAVR exceeded $60 000 at 6 to 12 months postoperatively …”
Section: Discussionmentioning
confidence: 98%
“…Short-term follow-up also revealed risks of cardiovascular events. 10 Despite the increased risk of cardiovascular events brought by RA, there is still no consensus for treatment for patients with aortic stenosis and connective tissue disease such as RA. However, a 2021 study showed that TAVR is a viable solution even for patients with both connective tissue disease and high surgical risk.…”
Section: Discussionmentioning
confidence: 99%
“…Trials such as PARTNER 1A show that the risk of neurological events after SAVR is lower than TAVR at 2.4% and 4.3% at 30 days and 1 year, respectively. 10 However, these studies did not specifically include patients with RA, who are at higher risk of calcification and progression of aortic stenosis and therefore may have a higher risk of postoperative neurological events.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute‐phase responses were associated with more rapid progression of aortic stenosis in an RA cohort, rates of progression were no greater than those observed among patients in previous non‐RA cohorts (32). Finally, patients with RA may have higher mortality rates following surgical aortic valve replacement (33). These novel findings of increased mortality related to valvular heart disease in RA call for clinical and epidemiologic investigations to better characterize valvular disorders in RA.…”
Section: Discussionmentioning
confidence: 99%